RATIONALE OF CONSTRUCTION OF HYDRO-SPRAYING INSTALLATION OF TUNNEL TYPE - Радіоненко, В. М.; П’янкова, Ю. В.; Кочетов, В. П. (Scientific Progress & Innovations, 2013)
The aim of the paper is to confirm the effectiveness of the structural choice of membrane for the application of additional factor of impact SCI lettuce during storage at refrigerated cargo spaces. In the course of experimental studies modules with semi-polymeric membranes were used. Modified gas medium was formed as a result of gas exchange between the environment and lettuce into a confined space module, as well as between the environment and the outside air through the membrane material having selective permeability to gas medium components. Our studies confirm that the cooling storage technology using a modified gas medium (MGM) as an additional factor of influence is an effective means of reducing costs and increasing the duration of storage of perishable plant products in existing refrigerators APK of Ukraine. Scientific novelty is the optimal size of a semipermeable membrane of specific designs for specific varieties of lettuce leaves and a certain total weight of the package, which justifies further research to choose the best alternative design solutions for the implementation of MGM membranes, taking into account the properties of other types of crop production. These results suggest the feasibility of using a modified gas medium (MGM) to prolong the storage of perishable plant products as applying to existing refrigerators does not require the introduction of structural changes and of additional use of equipment.